Outward foreign direct investment and domestic innovation performance: Evidence from China. Issue 5 (October 2016) - Li, Jian; Strange, Roger; Ning, Lutao; Sutherland, Dylan
Highlights: This paper studies the effects of OFDI on regional innovation performance. We use a panel of Chinese provinces and GMM estimation method. We confirm that OFDI has a very significant impact on domestic innovation. Foreign presence and local competition play moderating roles. Abstract: Recent years have witnessed substantial outward foreign direct investment (OFDI) from many emerging economies. Should the governments of these economies encourage OFDI in order to promote domestic innovation? Much OFDI by emerging economy multinational enterprises (EMNEs) has been undertaken to acquire strategic assets overseas, but do these acquisitions bring innovation benefits at home? The empirical analysis presented in this paper considers the effects of OFDI on regional innovation performance, using a panel of Chinese provinces, and finds that OFDI has a very significant impact on domestic innovation. Furthermore, we also identify three contingent factors – absorptive capacity, foreign presence, and the competition intensity of the local market – that moderate the impact of OFDI on innovation performance.